If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(3p + 5) + -2(1 + -11p) = 3(7 + 4p) Reorder the terms: -3(5 + 3p) + -2(1 + -11p) = 3(7 + 4p) (5 * -3 + 3p * -3) + -2(1 + -11p) = 3(7 + 4p) (-15 + -9p) + -2(1 + -11p) = 3(7 + 4p) -15 + -9p + (1 * -2 + -11p * -2) = 3(7 + 4p) -15 + -9p + (-2 + 22p) = 3(7 + 4p) Reorder the terms: -15 + -2 + -9p + 22p = 3(7 + 4p) Combine like terms: -15 + -2 = -17 -17 + -9p + 22p = 3(7 + 4p) Combine like terms: -9p + 22p = 13p -17 + 13p = 3(7 + 4p) -17 + 13p = (7 * 3 + 4p * 3) -17 + 13p = (21 + 12p) Solving -17 + 13p = 21 + 12p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-12p' to each side of the equation. -17 + 13p + -12p = 21 + 12p + -12p Combine like terms: 13p + -12p = 1p -17 + 1p = 21 + 12p + -12p Combine like terms: 12p + -12p = 0 -17 + 1p = 21 + 0 -17 + 1p = 21 Add '17' to each side of the equation. -17 + 17 + 1p = 21 + 17 Combine like terms: -17 + 17 = 0 0 + 1p = 21 + 17 1p = 21 + 17 Combine like terms: 21 + 17 = 38 1p = 38 Divide each side by '1'. p = 38 Simplifying p = 38
| (x+9)18=12/72 | | -7(3+3b)=-6-6b | | (5p-2)-(2p+7)+(-9p+18)= | | 2y+5=-4-4 | | -2(8x+2)=4(x+6.5) | | 8x-7=42 | | (19b-3)-9(2b+3)=-5 | | x^2+y^2-10x-14y+58=0 | | 3(2+2n)-6(n+2)=-6 | | -3+12=-6-18 | | 4(3x-3)=-8(x+14) | | -(n+3)=72 | | 9x+5x+4+9=4x+4+9x | | -3-4(3+5p)=-155 | | [7-4x]=5 | | 3/5(5m+15)=12 | | 12-3=m+4 | | 10(4x+10)=4(x+7) | | -0.25+1.75x=-1.75+2.25x | | -7+2r=-7+5r | | (7+4i)*(7+4i)= | | 7x+8=232 | | 2(24x-3.2)=4(10x+4.5) | | (2x+20)(6x-38)= | | -8(z-6)=-8z-7 | | 2k-3=15 | | 1762=598-24.25a | | 2-6b=-58 | | 11x-66x=5x | | 5.1-7p=(-9.9) | | 3b+b+40= | | -3x+2.5=1.5(x+4) |